The unfolding water drama in the Anthropocene: towards a resilience-based perspective on water for global sustainability - Rockström, Johan; Falkenmark, M.; Allan, T.; Folke, C.; Gordon, L.; Jagerskog, A.; Kummu, M.; Lannerstad, Mats; Meybeck, M.; Molden, David J.; Postel, S.; Savenije, H.H.G.; et al. (Wiley, 2014)
The human influence on the global hydrological cycle is now the dominant force behind changes in water resources across the world and in regulating the resilience of the Earth system. The rise in human pressures on global freshwater resources is in par with other anthropogenic changes in the Earth system (from climate to ecosystem change), which has prompted science to suggest that humanity has entered a new geological epoch, the Anthropocene. This paper focuses on the critical role of water for resilience of social-ecological systems across scales, by avoiding major regime shifts away from stable environmental conditions, and in safeguarding life-support systems for human wellbeing. It highlights the dramatic increase of water crowding: near-future challenges for global water security and expansion of food production in competition with carbon sequestration and biofuel production. It addresses the human alterations of rainfall stability, due to both land-use changes and climate change, the ongoing overuse of blue water, reflected in river depletion, expanding river basin closure, groundwater overexploitation and water pollution risks. The rising water turbulence in the Anthropocene changes the water research and policy agenda, from a water-resource efficiency to a water resilience focus. This includes integrated land and water stewardship to sustain wetness-dependent ecological functions at the landscape scale and a stronger emphasis on green water management for ecosystem services. A new paradigm of water governance emerges, encouraging land-use practices that explicitly take account of the multifunctional roles of water, with adequate attention to planetary freshwater boundaries and cross-scale interactions.